Advertisement Remove all ads

Solve the Following Equation: (X - 5)(X + 3) = (X - 7)(X + 4) - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

Solve the following equation:

(x - 5)(x + 3) = (x - 7)(x + 4)

Advertisement Remove all ads

Solution

(x - 5) (x + 3) = (x - 7)(x + 4)

⇒ x2 + 3x - 5x - 15 = x2 + 4x - 7x - 28

⇒ -2x - 15 = - 3x - 28

⇒ 3x - 2x = 15 - 28

⇒ x = -13

Concept: Simple Linear Equations in One Variable
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 14 Linear Equations in one Variable
Exercise 14 (A) | Q 17 | Page 165
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×